Introducing one new genus and two new species of Psathyrellaceae (Basidiomycota, Agaricales), with notes on Candolleomyces and Ephemerocybe - Yang, Kun L.; Lin, Jia Y.; Li, Guang-Mei; Yang, Zhu L. (Phytotaxa, 2025)
During an investigation on psathyrelloid fungi conducted from 2023 to 2024 in the Pearl River Delta in South China, 49 collections were gathered and studied through morphological observations and phylogenetic analyses. Among these collections, eight are identified as a new species of a new genus, namely Cantonopsathyra serendipita, characterized by terrestrial psathyrelloid basidiomata with a slightly rugose pileus, basidiospores with an irregularly wrinkled surface, and the rare presence of pleurocystidia and clamp connections; two are identified as a new species of Parasola, namely Pa. haizhuensis, characterized by lignicolous psathyrelloid basidiomata with an undulate pileus margin; while the remaining 39 could only be identified to the generic level of Candolleomyces. Species delimitation within Candolleomyces is found to be challenging, because the following problems often occur in the hypothetical species on our ITS phylogeny: (1) with an ITS sequence more than 99% similar to that of another species; (2) issued by a very short branch from the backbone; (3) unsupported by statistical values; (4) not a monophyletic group; and (5) with inaccurate sequences. A four-locus (ITS, nrLSU, tef-1α, and β-tub) phylogenetic analysis with limited samples of Candolleomyces appears to alleviate most of these problems by providing clearer partitions; however, four-locus data for previously proposed species remain largely unavailable for comparison. Based on the recent scale of species delimitation in Candolleomyces, more than ten new species of Candolleomyces appear to exist in our collections; however, due to the aforementioned issues, they are not formally proposed in this study. We recommend that new species of Candolleomyces proposed in the future should be provided with four-locus data of ITS, nrLSU, tef-1α, and β-tub. Supplementary sequencing for unprovided loci from type materials of previously proposed Candolleomyces species, particularly those proposed in recent years, is also highly encouraged. The recently proposed genus Tulosesus is illegitimate due to its circumscription including the type of an earlier legitimate genus, Ephemerocybe, and corresponding new combinations for transfer are made. Another genus, Lacrymaria Pat. 1887, is also illegitimate due to the homonymy with an earlier protist genus, Lacrymaria Ehrenberg 1830, but may be worth conserving; therefore, it is not treated here.